New explicit correlation to compute the friction factor under turbulent flow in pipes - Alan Olivares Gallardo; Rodrigo Guerra Rojas; Marco Alfaro Guerra (Revista Brasileira de Engenharia Agrícola e Ambiental)
HIGHLIGHTS The correlation facilitates the calculation of head losses in hydraulic systems. The correlation was design for regimes of high and low turbulence. The best performance of the correlation is obtained for a range of roughness that goes from 10-2 to 5 × 10-3.